Efficacy and tolerability of a specialized dietary therapeutic product in long-chain and very long-chain fatty acid metabolism disorders in children - N.A. Semenova; E.A. Shestopalova; S.I. Kutsev (LCC «Medicine-Inform», 2021)
Aim: to assess the efficacy and tolerability of a specialized dietary therapeutic product in long-chain and very long-chain fatty acid metabolism disorders in children. Patients and Methods: this open-label prospective uncontrolled study enrolled 5 children aged 35 ± 14 months who were diagnosed with long-chain and very long-chain fatty acid metab-olism disorders. Diet therapy using the tested product ("Monogen") was prescribed and corrected after the analysis of actual diet. Physical development and neurological status were evaluated, blood levels of specific acyl-carnitines (С16-ОН, С18-ОН, С18:1-ОН, С14:1, С14) were measured. Tolerability was assessed by the rate and severity of adverse events (including allergic reactions) and the changes in vital functions compared to baseline. Patient and doctor satisfaction was evaluated using a questionnaire. Results: children received the tested product throughout the study (30±2 days). The lev-els of acyl-carnitines were within normal ranges in all children. No dyspepsia, allergic reactions, somatic dysfunction, or neurological deviations were reported. Physical exam consistently fell in the range of normal for age. Parents and doctors were fully satisfied with the tested product ("Monogen"). Conclusions: "Monogen" is highly effective for therapeutic feeding of children with long-chain and very long-chain fatty acid metabolism disorders. Keywords: long-chain fatty acid oxidation disorders, β-oxidation of fatty acids, long-chain acyl-coA dehydrogenase deficiency, biallelic mutation, therapeutic feeding.